Evaluating the Role of Sustainable Leadership and Technology Integration in Enhancing the Environmental and Social Responsibility of the UAE Banking Sector - Al Aina, Riham; Faisal, Rouhi (Archives of Business Research, 2024)
This paper analyzes the role of sustainable leadership and technology integration in increasing the environmental and social responsibility of the UAE banking sector. Banks are prominent agents in creating sustainability through their financing activities and processes. Sustainable leadership is more than pursuing profit motives; it includes moral and inclusive decision-making for positive environmental and social impact. Sustainable leadership and enabling technologies contribute to a bank’s sustainability indicators. A qualitative literature review combined the scholarly views in this field. Twenty recent peer-reviewed papers were thematically analyzed. This revealed how sustainable bank leaders adopt collaborative approaches involving stakeholders in creating sustainability solutions. Their values-based leadership focuses on long-term impacts and integrating environmental and social factors in bank strategies. Sustainability technologies like AI, big data and blockchain offer tools to implement these strategies. The analysis found that technology aids sustainable leaders in improving banks’ eco-efficiency, reducing emissions, managing risks, increasing renewable financing and enabling financial inclusion. This enhances their environmental and social responsibility. Stakeholders like customers, employees and investors generally favour such sustainability integration. However, concerns exist around potential tradeoffs, profitability impacts and the depth of banks’ commitment. The review also uncovered implementation challenges, including costs, data deficiencies, staff capabilities and cultural change. Smaller banks significantly lag more prominent entities. Radical strategic realignment rather than incremental changes is required. Public policy plays a crucial role through reporting requirements, emission limits and support frameworks. The limitations of this qualitative synthesis point to future research directions. Statistical meta-analyses could increase the generalizability of findings. Surveys and interviews with experts would provide rich primary data. Comparative analyses of technologies and leadership styles driving the most robust sustainability results would reveal best practices. Longitudinal studies can elucidate the evolution of banks’ sustainability approaches over time. In-depth case studies of smaller banks would uncover constraints and potential solutions for mainstreaming sustainability. Action research pilots can test mechanisms to instil sustainable leadership thinking. Policy analyses can identify regulatory measures to accelerate progress. In conclusion, sustainable leadership and technology integration are essential enablers, but not guarantees, of elevating bank sustainability. Realizing their transformative potential requires bank leaders to move from rhetoric to resolute, broad-based action. This necessitates radical strategic reorientation, not just incremental improvements. Multi-stakeholder collaboration is vital, alongside supportive public policies and ongoing research. Sustainable leadership and technologies must remain central in catalyzing a systemic transition towards responsible banking aligned with urgent sustainability imperatives.